English teachers’ perceptions of emergency remote teaching: Emotional attitudes, professional identity, and coping strategies - Huang, Fang; Zhao, Mingyan; Qi, Jiafu; Zhang, Ruyue (Frontiers in Psychology, 2023)
While the technology integration has been widely acknowledged, the insufficient effort has been made to understand English teachers’ perceptions of mobile-assisted emergency remote teaching (ERT). This study inquired into experienced English teachers’ emotional attitudes, perceptions of the reconstructed professional identity, and their strategies to cope with difficulties when conducting ERT in the Chinese English teaching context. Semi-structured interviews were conducted among five experienced universities English teachers in China. The findings indicated a trajectory of teachers’ attitudes towards ERT, namely, their attitudes were switched from doubt and rejection to fondness and attachment. Experienced English teachers adopted various strategies to cope with the difficulties and challenges they have encountered, including seeking support from their peers, students, and family, as well as self-regulated learning to sustain continuing professional development. During ERT, they have reconstructed their teacher identities. The study enriched peoples’ understanding of technology-enhanced language teaching and learning by contextualizing the study in the Chinese ERT context. Results can provide empirical evidence for policymakers to make informed decisions.